Preservation of cross-bred boar semen - PANDE, GAURAV; BHATTA, V K; THAKUR, M S (The Indian Journal of Animal Reproduction, 2023)
Twenty four semen samples having more than 75 per cent progressively motile spermatozoa were obtained from six cross-bred boars (Large White yorkshire X Indigenous). The part of neat semen was diluted at the rate of 1 :2 with each of four dilutors viz. Glucose Potassium sodium tartrate Sodium citrate dihydrate Edate (GPSE-1), Kiev dilutor, Beltsville Liquid (BL-1) and Beltsville Thawing Solution (BTS) and preserved at 15°C. The progressive motility of spermatozoa in the preserved semen was assessed at 0, 24, 48 and 72 hours after preservation to compare the efficacy of the dilutors. GPSE-1 dilutor maintained better sperm motility than other dilutors at each hour of preservation. The percent motile spermatozoa in GPSE-1 dilutor was 84.81 ± 0.17, 75.71 ± 0.27, 70.0 ± 0.33 and 59.9 ± 0.64 at O hour, 24 hour, 48 hour and 72 hour of preservation, respectively. Only GPSE-1 and BTS dilutors maintained over 50 percent motile spermatozoa upto 72 hours after preservation. The EDT A, Potassium sodium tartrate and Sodium citrate dihydrate in GPSE-1 dilutor worked synergistically and maintained sperm motility for longtime.